Contra Semi*δ-Continuous Functions in Topological Spaces - S. Pious Missier; C. Reena; G. Mahadevan (International Journal of Mathematics And its Applications, 2017)
In this paper we define contra-semi*δ-continuous, contra-semi*δ-irresolute, semi*δ-open and semi*δ-closed functions and investigate their properties.